Representasi Etika Jurnalistik Investigasi Dalam Film Shattered Glass Karya Billy Ray (Analisis Semiotika Roland Barthes) - Selvia Puspita Ningsih; Nurseri Hasnah Nasution; Jufrizal (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
Good and correct reporting must be in harmony with journalism ethics by prioritizing social responsibility to serve the information needs of society. This research is entitled, "Representation of Investigative Journalistic Ethics in Billy Ray's Shattered Glass Film (Roland Barthes Semiotic Analysis)". It tells the story of the internal problems of New Republik magazine in 1998, when Glass did journalistic work that was not based on a journalistic code of ethics which resulted in him being fired from his job. The writer calls Glass' behavior in this film as "imaginary journalism" or in the film it is called "storyteller journalism", engineering an event just for self-famousness. The research methodology in this research is qualitative with Roland Barthes' semiotic analysis approach. Research only focuses on each scene that refers to the 5 points of the code of ethicsInternational federation of Jounalist (IFJ) namely (truth, freedom, legality, correcting mistakes and obeying the law), then analyzing the meaning of denotation, connotation and myth in the scene. The conclusion of the analysis is that the scene in the film Shattered Glass that seems to apply a code of ethicsInternational federation of Jounalist (IFJ). Journalists in online media as well as journalists at the editorial office of The New Republik magazine conduct honest investigations, try to obtain documents legally, be careful when processing data obtained, respect sources and prioritize the interests of the community, and remain firm and independent.